Konflik Batin Tokoh Utama dalam Novel Kata Karya Rintik Sedu - Muhlason, Moch (Jurnal Simki Pedagogia, 2021)
This study examines the inner conflict of the main character Binta. The purpose of this study is to describe the inner conflict of the main character regarding the id, ego, and superego in the word novel by Rintik Sedu. The method used is a qualitative method. The approach used is a literary psychological approach. The data in this study are in the form of novel quotes that contain inner conflicts. The data source in this research is the novel Kata by Rintik Sedu. The data collection technique used in this study is a literature study technique by reading carefully and repeatedly so as to understand the full meaning of the novel which is the object of the author's study based on the formulation of the problem and the objectives of this study. The data analysis technique used in this study prepares and organizes data such as transcript text data, then reduces the data into themes through the process of coding and summarizing the code. The last step is to present the data in the form of charts, tables or discussions. The results showed that the inner conflicts of the main characters in the word novel by Rintik Sedu were as follows, anger, hope, optimism, motivation, awareness, annoyance, sadness, disappointment, patience, wisdom, compassion, regret and guilt.